Biomechanical analysis of femoral stems in hinged total knee arthroplasty in physiological and osteoporotic bone. (January 2022) - Bori, Edoardo; Armaroli, Federica; Innocenti, Bernardo
Highlights: Longer stems guarantee better fixation compared to short ones; however, they induce higher stress-shielding effect in the distal region of the femur (greater for press-fit stems). Cemented configurations (especially with stems of 50 mm and 95 mm of lengths) induce lower micromotions compared to their respective press-fit configurations. Osteoporotic Risk of Fracture values are greater than the physiological ones but always below the limit of fracture. When selecting a femoral stem in a hinged TKA to achieve proper stability and bone stress, the surgeons should consider, when possible, short cemented stems. Abstract: Background and Objective: Adequate fixation is a requisite for hinged Total Knee Arthroplasty (TKA): consequently, several stem solutions are currently available. However, there are no evidence-based biomechanical guidelines for surgeons to determine the appropriate stem length and whether to use cemented or press-fit fixation. The objective of this study is therefore to compare, using a validated finite-element model, bone stresses and implant micromotions in different configurations. Methods: The 3D bone geometries were obtained from CT-scans reconstruction and the 3D model components of an Endo-Model Rotating Hinge (WALDEMAR LINK GmbH & Co. KG, Hamburg, Germany) were generated from industrial designs provided by the manufacturer. Sixteen configurations were investigated considering four stem lengths (50, 95, 120, 160 mm), cemented and press-fit fixation and physiological and osteoporotic bone properties. A further configuration without stem was analyzed as control. Average Von-Mises stresses, risk of fracture and micromotions were extracted in several regions of interest at 0° and 90° of flexion, under physiological load conditions. Results: Generally, longer stems guarantee better fixation compared to short ones; however, they induce higher stress-shielding effect in the distal region of the femur (even greater for press-fit stems, with values up to 38.5% greater than cemented ones). The cemented configurations, especially in case of 50 mm and 95 mm lengths, induce lower micromotions (down to 16% lower) compared to their respective press-fit configurations. The osteoporotic RF values were greater than the physiological ones (up to 20.5%), but always below the bone limit of fracture. Conclusions: According to this study, when surgeons need to select a femoral stem in a hinged TKA aiming to proper stability and bone stress, the preferable option would be short cemented stems.